2020
DOI: 10.1098/rstb.2019.0614
|View full text |Cite
|
Sign up to set email alerts
|

Faecal parasites increase with age but not reproductive effort in wild female chimpanzees

Abstract: Energy investment in reproduction is predicted to trade off against other necessary physiological functions like immunity, but it is unclear to what extent this impacts fitness in long-lived species. Among mammals, female primates, and especially apes, exhibit extensive periods of investment in each offspring. During this time, energy diverted to gestation and lactation is hypothesized to incur short and long-term deficits in maternal immunity and lead to accelerated ageing. We examined the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 88 publications
(99 reference statements)
1
14
0
Order By: Relevance
“…For example, a focal author with a positive ‘adjusted network size’ score would have more unique co-authors than expected, given their number of publications. Note that this residual regression approach [ 26 , 46 ] is not the same as the much criticized ‘regression of residuals' practice [ 47 ], since here we regress the predictors, rather than the response variable. For comparison, analyses using unadjusted metrics of collaboration behaviour are included in the electronic supplementary material, appendix 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a focal author with a positive ‘adjusted network size’ score would have more unique co-authors than expected, given their number of publications. Note that this residual regression approach [ 26 , 46 ] is not the same as the much criticized ‘regression of residuals' practice [ 47 ], since here we regress the predictors, rather than the response variable. For comparison, analyses using unadjusted metrics of collaboration behaviour are included in the electronic supplementary material, appendix 1.…”
Section: Methodsmentioning
confidence: 99%
“…Here we borrow concepts from studies testing how sociality relates to fitness and survival in non-human animals to investigate how collaboration patterns may influence career progression. For many species, interacting with peers is a crucial component of lifetime fitness [ 26 , 27 ] and lifespan [ 27 ]. Group-level cooperation improves acquisition of resources (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this volume, Jasienska [104] advocates for evolutionarily informed approaches to design more powerful studies of the health effects of reproduction, including more realistic assessments of reproductive effort. However, using detailed measures of reproductive effort, Phillips et al [92] found that wild chimpanzee females experienced only transient increases in faecal parasites during pregnancy, and high fertility predicted lower, not higher parasitism with age. This is surprising because, unlike humans, chimpanzees do not receive support from others to raise their offspring, suggesting instead that they may have effective strategies to resist the trade-offs between reproduction and health.…”
Section: (D) Sex Differences In Ageingmentioning
confidence: 99%
“…Two other papers translate clinical approaches to frailty to field conditions, examining ecologically relevant measures of physical performance in wild chimpanzees [90] and African foragers and pastoralists [91]. Other papers test for immunosenescence, which is difficult to measure directly in wild primates, but is detectable through its functional outcomes: age-related increases in parasitic [92] and viral infections [93]. Others have taken the opposite approach of dissecting complex phenomena like cognitive [94,95]), neurobiological [96] and skeletal ageing [97] to examine whether they result from common mechanisms across species.…”
Section: Key Themes From This Volumementioning
confidence: 99%
See 1 more Smart Citation